Kurangnya halal awareness pada masyarakat terhadap produk kosmetik - maghfiroh, ulfa (Maliki Interdisciplinary Journal, 2025)
This study examines the influence of halal awareness on public purchasing interest in cosmetic products. Halal awareness is a Muslim's understanding of the concept of halal, encompassing knowledge of raw materials and production process standards in accordance with Islamic law. Low halal awareness in the community is influenced by several factors, such as the level of religious understanding, implicit trust in Muslim-dominated markets, and difficulty in identifying halal products. Key findings indicate that cosmetic purchasing decisions are more significantly influenced by brand awareness than by the halal label. This indicates that consumers tend to rely on brand reputation as a guarantee of quality and safety, while literacy regarding the urgency of halal certification from official institutions such as LPPOM MUI still needs to be improved. From an Islamic perspective, the use of cosmetics containing haram or hazardous ingredients such as mercury is prohibited. Therefore, consumers are advised to be wise in choosing products that have been verified as halal and registered with the BPOM. Furthermore, the application of the principles of honesty and transparency in marketing strategies is key to ensuring that halal cosmetic products are well-received by the wider community.